Implementasi Model PJBL (Project Based Learning) Mata Kuliah Microteaching Dalam Meningkatkan Keterampilan Mengajar Guru SD - Regina Sipayung; Meikardo Samuel Prayuda; Natalia Ginting; Silvia Anggreni Br Surbakti; Anastasya Apriliaty Simamora; Gilberdh Saragih; Martina Siahaan (Departement of Mathematics Education, 2024)
PGSD students must be ready to establish their profession as teachers, for this they must be supported by knowledge and proven theories. This further strengthens the parties' trust in the teaching profession. One of the scientific methods for testing the truth of knowledge, theories or concepts in teacher training, especially those related to learning such as tests (experiments) which are expected so that they can implement existing learning in elementary schools. Schools can implement and design learning models related to teaching skills to elementary school students. One of the factors determining the success of learning is students' mental participation in learning through the opportunity to experience certain conditions or situations as they really are (experiential learning). This participation makes learning interesting and meaningful for students.